2019
DOI: 10.1016/j.jand.2018.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Foods and Beverages Obtained at Worksites in the United States

Abstract: Background-Nutrition interventions are a common component of worksite wellness programs and have been recognized as an effective strategy to change employee dietary behaviors. However, little is known about worksite food behaviors or the foods that are obtained at workplaces at the national level. Objective-The aims were to examine the frequency of obtaining foods at work among employed US adults and the amount of money spent obtaining them, determine the foods most commonly obtained at work, and assess the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 12 publications
(14 reference statements)
0
28
0
6
Order By: Relevance
“…Over the past decade, eating outside the home has been highlighted as one of the many factors contributing to poor dietary habits worldwide. Studies have shown that eating outside the home is associated with higher energy and fat intake, lower micronutrient intake [3][4][5][6][7], increased body fat and weight gain [8][9][10][11]. The average energy content of main meals served in both fast food and full service restaurants exceed public health recommendations (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, eating outside the home has been highlighted as one of the many factors contributing to poor dietary habits worldwide. Studies have shown that eating outside the home is associated with higher energy and fat intake, lower micronutrient intake [3][4][5][6][7], increased body fat and weight gain [8][9][10][11]. The average energy content of main meals served in both fast food and full service restaurants exceed public health recommendations (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The term “free food” was most appropriately used in describing this concept; however, no definition of the term was found. Onufrak, Zaganjor, Pan, et al (2019) contributed the first quantitative examination of foods and beverages commonly acquired by employees in the workplace (both purchased and free). In this work, the authors named the food acquired without employee monetary costs as “free food.” “Free food” was mentioned in three separate studies that examined the workplace dietary behaviors of low-wage workers, but the term was not described or studied further (Blake et al, 2009; Strickland et al, 2015; Tabak et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Free food at work was a socially accepted currency that was exchanged for many reasons and from many sources. The types of free foods were often indulgent comfort foods, which were more desirable in stressful work environments thus impacting the influence on employee dietary behaviors (Clohessy et al, 2019; Horton Dias & Dawson, 2020; Onufrak, Zaganjor, Pan, et al, 2019; Strickland et al, 2015; Tabak et al, 2018).…”
Section: Defining Attributes Of Free Food At Workmentioning
confidence: 99%
See 2 more Smart Citations